A fluorescence enhancement-based label-free homogeneous immunoassay of benzo[a]pyrene (BaP) in aqueous solutions. (May 2016) - Li, Taihua; Choi, Yo Han; Shin, Yong-Beom; Kim, Hwa-Jung; Kim, Min-Gon
Abstract: A fluorescence enhancement-based immunoassay has been developed for the detection of the polycyclic aromatic hydrocarbons (PAH), benzo[a]pyrene (BaP), in aqueous solutions. The results of this study show that BaP, which inefficiently fluoresces in aqueous solution, displays enhanced fluorescence when bound to the anti-BaP antibody (anti-BaP), as part of a label-free immunoassay system. Binding to anti-BaP results in a 3.12-fold increase in the fluorescence intensity of BaP, which emits at 435 nm when excited at 280 nm, due to the hydrophobic interaction and fluorescence resonance energy transfer (FRET) between antibody and antigen. As result of this phenomenon, the antibody-based fluorescence immunoassay system can be used to detect BaP specifically with a limit of detection (LOD) of 0.06 ng mL −1 . Finally, extraction recoveries of BaP from spiked wheat and barley samples were found to be in the range of 80.5–87.0% and 92.9–92.1%, respectively. Highlights: Fluorescence enhancement and FRET-based immunoassay of benzo[a]pyrene (BaP) was developed. Binding to the anti-BaP resulted in a 3.12-fold increase in the fluorescence intensity of BaP. The assay can be used to detect BaP specifically with a limit of detection of 0.06 ng mL −1 .